Aplikasi Penginderaan Jauh Untuk Identifikasi Bentuk DAS Serang Di Kulon Progo - Ignatius Adi Prabowo (PROMINE, 2017)
The aims of this research is to determine the shape of Serang drainage basin, Kulon Progo, DIY baseon the appearance recorded on the image of SRTM. Research method of remote sensing imageinterpretation of SRTM for the determination of Serang drainage basin and then calculate themorphometry of drainage basin in terms of the length of the main river, the width of the drainage basin,and the around of the drainage basin by using ArcGIS software. The results of morphometriccalculations is the main river length of 27.25 km, the drainage basin area 305.404 km2, the around ofdrainage basin 107.353 km. Based on these results can be calculated wide drainage basin of 11.207km, the shape of roundness 0.33 so that the Serang drainage basin is classified as a drainage basinwith elongated shape.